Epistemik dasar klasifikasi bibliografi pertama di China - Salnia Salnia (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
This paper aims to understand the basis of the classification applied epistemic first library catalog China, the seven epitomes (Qilue). Design / methodology / approach - Derived from the theoretical attitude that puts knowledge in social enterprise organizations, this study applies a multifaceted framework related to five categories of textual data: seven epitomes; biographical information on the Liuxin k and inteleasifikasi relevant